A review of thermal performance in multiple evaporators loop heat pipe. (October 2018) - Qu, Y.; Wang, S.; Tian, Y.
Highlights: The first review on Multiple Evaporators LHP (ME-LHP) developments for the past 20 years. Three key design issues for a ME-LHP design are discussed. The control rules of steady operation temperature in ME-LHP are reviewed. Required superheat for ME-LHP start-up is analyzed. Abstract: Multi-evaporator loop heat pipe (ME-LHP), as one of the typical two-phase closed capillary circulation systems, exhibits tremendous potential in applications which involve high heat flux and multi-heat sources, and is especially attractive to spacecraft and electronics packaging thermal control. This paper provides a comprehensive review of ME-LHP research and developments for the past 20 years covering four aspects: design theory, mathematical models, steady-state operational performance and start-up performance. ME-LHP design theory contains three key problems including the number limit for evaporators, sizing of the compensation chamber (CC) and calculation of the working fluid charge. Three peculiar features in steady performance have been discussed, which are the heat load sharing feature, the control rules of the operation temperature among multiple CCs, and the capillary limit of ME-LHP. Two influencing factors of start-up performance have been taken into account, including the required superheat on ME-LHP start-up and the initial fluid distribution in evaporators.